SPE Improved Oil Recovery Conference 2016
DOI: 10.2118/179702-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Surfactants and Co-Solvents Increase Oil Recovery and Reduce Cost

Abstract: The ability to develop high performance, low cost chemical formulations for chemical EOR involves the use of not only highly efficient surfactants tailored to specific crude oil and reservoir conditions, but also the technical know-how for combining the surfactants and other chemicals to create the best formulation as a complete package. Scientific understanding of how the molecular structures of surfactants and co-solvents affect microemulsion properties greatly speeds up the process of arriving at optimal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Lu et al (2014) successfully tested Guerbet carboxylates at high-temperature, high-salinity conditions using phase behavior, aqueous stability and coreflooding tests. Upamali et al (2016) reported up to 90% oil recovery post-waterflood at 68 °C using a blend of ethoxylated propoxylated carboxylates and IOS. Abalkhali et al (2019) reported tertiary oil recovery up to 90% in ASP corefloods using a blend of ethoxylated propoxylated carboxylates and IOS for carbonate rock at 100 °C and 60,000 ppm salinity.…”
Section: Aqueous Stability and Microemulsion Phase Behavior Testsmentioning
confidence: 99%
“…Lu et al (2014) successfully tested Guerbet carboxylates at high-temperature, high-salinity conditions using phase behavior, aqueous stability and coreflooding tests. Upamali et al (2016) reported up to 90% oil recovery post-waterflood at 68 °C using a blend of ethoxylated propoxylated carboxylates and IOS. Abalkhali et al (2019) reported tertiary oil recovery up to 90% in ASP corefloods using a blend of ethoxylated propoxylated carboxylates and IOS for carbonate rock at 100 °C and 60,000 ppm salinity.…”
Section: Aqueous Stability and Microemulsion Phase Behavior Testsmentioning
confidence: 99%
“…Through this interaction, the surfactant molecule decreases the interfacial tension of the crude oil thereby increasing crude oil mobility and oil recovery [7][8][9][10][11][12][13][14][15]. Though various conventional surfactants are proven to provide effective results with respect to their interaction with the crude oil in reservoirs for incremental oil recovery [16][17][18][19][20][21][22], the primary problem associated with this method is the environmental issue encountered during post implementation stage. As most of the conventional surfactants used in this method are anionic and derived from petrochemicals, these chemicals possess a molecular structure that can harm the aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Triglyceride oils such as from palm, coconut, sunflower, and Jatropha curcas have been utilized in various oil and gas exploration and production phases, such as in drilling (Adesina et al 2012;Fadairo et al 2013) and enhanced oil recovery operations as surfactants (Majidaie et al 2012;Mumtaz et al 2015;Soffian et al 2015;Karasinghe et al 2016;Nordiyana et al 2016) oil phases for drilling and completion fluids (Amanullah 2005;Okeke et al 2013;Yegin et al 2017) and corrosion inhibitors (Anand and Meenakshi 2011;Malarvizhi et al 2015;Rostron et al 2017) due to being non-toxic, biodegradable and possessing high viscosity, thermal stability, corrosion inhibition and effective interfacial tension alteration capabilities; these properties enable greater cutting carrying capability in drilling fluids (Fadairo et al 2013), better miscibility of fluids in flooding operations (Jeirani et al 2006) and prevention against deterioration of subsurface metal equipment (Mohadyaldinn et al 2017).…”
Section: Introductionmentioning
confidence: 99%